La percepción y satisfacción en el servicio al cliente en la librería éxito de la ciudad de Riobamba, período 2017. - Bonilla Mariño, José Daniel (2018)
The present research work was carried out in the period 2017 in the Éxito Bookstore which is dedicated to the commercialization of school supplies distributing wholesale and retail in the various sectors of Riobamba and its surroundings. Being a company well known for having the best products and topicality, quality and good treatment to people, this is why research focuses on the perception of how customers get their types, satisfaction their elements and service in the Customer Support. We worked with a base of the economically active population of 400 people of the city of Riobamba included in the age range from 18 to 65 years according to the INEC, the descriptive and field inductive method was applied with a non-experimental design. We used techniques and instruments such as surveys which helped us to know if the company meets their expectations and that should be changed to achieve the objectives set to meet their needs at the time of purchase and improve in terms of service being more agile and competitive in the market. That is why some service strategies have been suggested to improve the service provided, which is aimed at attracting new customers and their loyalty.